Megalithism and identity dialogues: texts, contexts and pretexts - Martins, Ana Cristina (2019)
Since at least the medieval time that the megalithic structures have aroused curiosity and pretexted various theories around its construction and functionality. With the beginning of the formative process of the ‘nation-states’, they became particularly interesting in visually marking the territory and referring to a certain pre-Roman ancestry. A preterit that was reinforced already in the 19th century, in reaction to the Napoleonic political project that legitimized subsequent national and regional identity affirmations. Portugal was no exception, not so much for the political assertion as for the need felt by the pioneers of archaeology in the country to fit into the ‘state of the art’ of European research regarding prehistoric archaeology. From then on, this theme no longer went beyond its horizons, but rather strengthened according to the prevalence of personal (rather than institutional) agendas. We will therefore proceed to a very brief analysis of some of the contexts that in Portugal have pretexted the production of texts on megalithic structures, from the end of the 19th century to the 3rd Archaeological Conference of the Association of Portuguese Archaeologists (1977).